2015
DOI: 10.1007/s00011-015-0848-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microRNA expression profiling in peripheral blood lymphocytes in rats with experimental autoimmune uveitis

Abstract: Our findings show that the differentially expressed miRNAs in EAU rats were closely associated with immune signaling pathways and may be applied in early prevention, prognosis and possible therapy in uveitis, indicating that miRNAs play an important role in the development of uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…, indicating that the response mechanism to uveitis may be involved in multiple signalling pathways. Moreover, our previous microRNA genomics analysis also revealed that the pathogenesis of uveitis is involved in the aberrant expression of microRNAs that can regulate the expression of messenger RNAs and further influence the expression of protein profiling, indicating that these aberrant microRNAs targeted genes were associated with multiple immune‐related signalling pathways . Therefore, our findings will provide additional insights into further investigating candidate genes for uveitis susceptibility.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…, indicating that the response mechanism to uveitis may be involved in multiple signalling pathways. Moreover, our previous microRNA genomics analysis also revealed that the pathogenesis of uveitis is involved in the aberrant expression of microRNAs that can regulate the expression of messenger RNAs and further influence the expression of protein profiling, indicating that these aberrant microRNAs targeted genes were associated with multiple immune‐related signalling pathways . Therefore, our findings will provide additional insights into further investigating candidate genes for uveitis susceptibility.…”
Section: Discussionmentioning
confidence: 62%
“…34 differentially expressed proteins were associated Histopathological characterization of rat eyes in both control and EAU subjects on day 11 post-immunization. Haematoxylin and eosin staining was performed for eye tissue sections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, recognition of differentially expressed miRNAs will facilitate the understanding of disease progression, uncovering the pathogenic role of miRNAs. Previous studies have revealed that some diseases are closely related to the abnormal expression and regulation of miRNA-targeted mRNAs [18][19][20]. It is reported that some miRNAs show differential expression in the sclera of rapidly growing fetal eyes at different ages, and thus playing a fundamental role in regulating ocular growth [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have used proteomic profiling to measure changes in EAU rat plasma compared with control samples, indicating that the pathogenesis of EAU is associated with the aberrant expression of proteins involved in multiple signaling pathways (3). Additionally, the development of EAU is also associated with the regulation of mRNAs by microRNAs (4).…”
Section: Introductionmentioning
confidence: 99%